Achieving mainstream anammox in biological aerated filter by regulating bacteria community structure. (December 2022) - Zhou, Tong; Liu, Xiuhong; Li, Haixin; Yang, Qing; Li, Jianmin; Gu, Pengchao; Guo, Jin
Graphical abstract: Highlights: One-stage PN-A was achieved in BAF by FA inhibition and bacteria competition. One-stage PN-A was much easier achieved than two-stage PN-A in BAF. Backwash regulated bacterial community structure in one-stage PN-A. Achieved mainstream anammox by alternated high/low NH4 + -N in the influent. Abstract: Although mainstream partial nitrification-anammox (PN-A) is a highly efficient and sustainable wastewater treatment process, it is difficult to achieve and stabilize due to the competition among functional bacteria. In this study, achieving one-stage mainstream anammox via regulating bacteria community structure was studied in a lab-scale biological aerated filter (BAF). The results showed that high free ammonia with 89.57 mg/L, nitrite nitrogen (NO2 − -N) competition between anammox bacteria (AnAOB) and nitrite oxidizing bacteria (NOB), and backwash regulated the bacteria community structure. After backwash, Candidatus Kuenenia became the dominant bacteria and the relative abundance increased to 5.56 %. In BAF, one-stage mainstream anammox with total nitrogen (TN) being lower than 15 mg/L in the effluent was achieved using lag-time of bacteria activity recovery caused by alternating operation of high and low ammonia nitrogen (NH4 + -N), which have great potential applied in municipal wastewater treatment plants (MWWTPs).